Validasi E-Modul Materi Termokimia Berbasis PBL untuk Menunjang Pembelajaran Kurikulum Merdeka Fase F Kelas XI SMA/MA - Elfiza, Rizma; Hardeli, Hardeli (Lembaga Yasin AlSys, 2024)
Thermochemical material is material that is difficult for students to understand, so students need innovative teaching materials that adapt to current developments and technology to support independent curriculum learning. One of the teaching materials that can be developed is a PBL-based e-module. The PBL model is used to help students be creative and think critically through the process of solving problems in the real world. This research aims to develop innovative teaching materials in the form of E-Modules so that they can improve students' critical thinking abilities and increase students' interest in learning. So a PBL-based thermochemical material e-module was developed to support independent curriculum learning for phase F class XI SMA/MA using the plomp development model. In the e-module validity test, the e-module validity value was 0.90 in the valid category.